Expression of Prostacyclin-Synthase in Human Breast Cancer: Negative Prognostic Factor and Protection against Cell Death In Vitro. (27th July 2015) - Klein, Thomas; Benders, Jens; Roth, Friederike; Baudler, Monika; Siegle, Isabel; Kömhoff, Martin
Abstract : Endogenously formed prostacyclin (PGI2 ) and synthetic PGI2 analogues have recently been shown to regulate cell survival in various cell lines. To elucidate the significance of PGI2 in human breast cancer, we performed immunohistochemistry to analyze expression of prostacyclin-synthase (PGIS) in 248 human breast cancer specimens obtained from surgical pathology files. We examined patients' 10-year survival retrospectively by sending a questionnaire to their general practitioners and performed univariate analysis to determine whether PGIS expression correlated with patient survival. Lastly, the effects of PGI2 and its analogues on cell death were examined in a human breast cancer cell line (MCF-7) and a human T-cell leukemia cell line (CCRF-CEM). PGIS expression was observed in tumor cells in 48.7% of samples and was associated with a statistically significant reduction in 10-year survival (P = 0.038 ; n = 193 ). Transient transfection of PGIS into MCF-7 cells exposed to sulindac increased cell viability by 50% and exposure to carbaprostacyclin protected against sulindac sulfone induced apoptosis in CCRF-CEM cells. Expression of PGIS is correlated with a reduced patient survival and protects against cell death in vitro, suggesting that PGIS is a potential therapeutic target in breast cancer.